Malay Translation of Attitudes Toward Career Counselling Scale for University Students in Malaysia - Ansarul Haq Tahrir Adli; Mohd Izwan Mahmud; Salleh Amat; Sheerad Sahid (Qubahan Academic Journal)
The purpose of this study is to translate the Attitudes Towards Career Counselling Scales (ATCCS) into Malay version. The researcher also tested the validity and reliability of the instrument using exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). A total of 500 final-year undergraduate students at four public universities in Malaysia were included in this study (100 for EFA, 400 for CFA). There are four experts involved in the translation process. The three experts consist of a university lecturer in the field of counseling and a translation specialist. The face and content validity of the instrument involved five experts and resulted in a high validity score of 0.95. Two factors were formed through EFA, namely value and stigma, based on an eigenvalue of above 1. The total cumulative percentage is 64.95% and is considered strong. All items have factor loading values above .6. The result of the CFA analysis shows that the ATCCS measurement model had fulfilled the fit index RMSEA (0.089), CFI (0.926), TLI (0.914) and Chisq/df (4.191). The results also show that convergent validity and composite reliability were achieved. These two factors have an internal consistency value (Cronbach's alpha) of value α =.95, stigma α =.88, total ATCCS α =.85, and these values are within an acceptable range. The conclusion from the EFA and CFA conducted is that the Attitudes Toward Career Counselling in the Malay version meets the criteria of validity and reliability of the instrument to be used by future researchers in determining students' planned happenstance skills among university students.